2022
DOI: 10.3390/ma15103672
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Self-Healing Evaluation of Asphalt Concrete Containing Encapsulated Rejuvenator

Abstract: Ultraviolet radiation, oxidation, temperature, moisture, and traffic loads produce degradation and brittleness in the asphalt pavement. Microcracks develop into macrocracks, which eventually lead to pavement failure. Although asphalt has an inherent capacity for self-healing, it is constricted. As a result, damages build beyond the ability of asphalt to repair themselves. This research employs the in-situ crack healing method of encapsulated rejuvenator technology to enhance the insufficient self-healing capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The fiber encapsulation ensures a higher likelihood of rejuvenator release into cracks due to the increased probability of cracks intersecting the fiber network [19]. However, this method's development is still nascent, necessitating further research to explore the impact resistance and efficacy of self-healing in fibers containing rejuvenators within bituminous materials [15,[20][21][22]. Currently, the microcapsule system remains the predominant method for encapsulating rejuvenators.…”
Section: Introductionmentioning
confidence: 99%
“…The fiber encapsulation ensures a higher likelihood of rejuvenator release into cracks due to the increased probability of cracks intersecting the fiber network [19]. However, this method's development is still nascent, necessitating further research to explore the impact resistance and efficacy of self-healing in fibers containing rejuvenators within bituminous materials [15,[20][21][22]. Currently, the microcapsule system remains the predominant method for encapsulating rejuvenators.…”
Section: Introductionmentioning
confidence: 99%
“…Asphalt has rheological properties and viscoelastic properties. After being damaged by external forces, micro-cracks and micro-pores inside asphalt can be closed under certain conditions so that asphalt performance can recover to a certain extent, which is called the self-healing property of bitumen [1][2][3][4][5]. Road workers can take advantage of this property to preconserve the asphalt pavement before macroscopic damage occurs to extend the service life of the pavement.…”
Section: Introductionmentioning
confidence: 99%
“…Rejuvenators are generally engineered cationic emulsifiers, which consist of a lubricant and extender oils with a high content of maltene. It is reported that vegetable oil can also be applied as an asphalt rejuvenator agent [ 10 , 11 ]. At the same time, methods to control parameters such as microcapsule particle size distribution, shell thickness, and shell strength have also been proposed [ 12 ].…”
Section: Introductionmentioning
confidence: 99%